Crack propagation in fracture mechanical graded structures - B. Schramm; H.A. Richard (Fracture and Structural Integrity, 2015)
The focus of manufacturing is more and more on innovative and application-oriented products considering lightweight construction. Hence, especially functional graded materials come to the fore. Due to the application-matched functional material gradation different local demands such as absorbability, abrasion and fatigue of structures are met. However, the material gradation can also have a remarkable influence on the crack propagation behavior. Therefore, this paper examines how the crack propagation behavior changes when a crack grows through regions which are characterized by different fracture mechanical material properties (e.g. different threshold values ?KI,th, different fracture toughness ?KIC). In particular, the emphasis of this paper is on the beginning of stable crack propagation, the crack velocity, the crack propagation direction as well as on the occurrence of unstable crack growth under static as well as cyclic loading. In this context, the developed TSSR-concept is presented which allows the prediction of crack propagation in fracture mechanical graded structures considering the loading situation (Mode I, Mode II and plane Mixed Mode) and the material gradation. In addition, results of experimental investigations for a mode I loading situation and numerical simulations of crack growth in such graded structures confirm the theoretical findings and clarify the influence of the material gradation on the crack propagation behavior. KEYWORDS. Functional fracture mechanical gradation; Crack propagation direction; TSSR-concept; Experimental investigations; Numerical simulations.